2017
DOI: 10.5194/bg-2017-17
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulating precipitation decline under a Mediterranean deciduous Oak forest: effects on isoprene seasonal emissions and predictions under climatic scenarios

Abstract: Abstract. Seasonal variations of Q. pubescens physiology and isoprene emission rates (ER)were studied from June 2012 to June 2013 at the O 3 HP site (French Mediterranean) under natural (ND) and amplified (+30%, AD) drought. While AD significantly reduced the stomatal conductance to water vapour over the season excepting August, it did not significantly limit CO 2 net assimilation, which was the lowest in summer. ER followed a 20 significant seasonal pattern, whatever the drought intensity, with mean ER maxima… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…A similar study was performed in 2012 (first year of AD) on isoprene emissions from the same trees (Genard‐Zielinski et al, ) and highlighted an increase in this compound, whereas we observed a decrease after the third and fourth years of AD. Decreases in isoprene emissions could be problematic for Q. pubescens as this compound is known to act as an antioxidant and maintain the stability of thylakoid membranes under oxidative conditions (Velikova et al, ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…A similar study was performed in 2012 (first year of AD) on isoprene emissions from the same trees (Genard‐Zielinski et al, ) and highlighted an increase in this compound, whereas we observed a decrease after the third and fourth years of AD. Decreases in isoprene emissions could be problematic for Q. pubescens as this compound is known to act as an antioxidant and maintain the stability of thylakoid membranes under oxidative conditions (Velikova et al, ).…”
Section: Discussionsupporting
confidence: 85%
“…antioxidant system.A similar study was performed in 2012 (first year of AD) on isoprene emissions from the same trees(Genard-Zielinski et al, 2017) and highlighted an increase in this compound, whereas we observed a decrease after the third and fourth years of AD.Decreases in isoprene emissions could be problematic for Q. pubescens as this compound is known to act as an antioxidant and maintain the stability of thylakoid membranes under oxidative conditions(Velikova et al, 2011). The antioxidant system of Q. pubescens could be affected by the isoprene decrease through compensatory mechanisms(Munne-Bosch, 2005), but this was apparently not the case because no strong trade-off (indicated by a negative correlation) was detected between isoprene and the major antioxidants (e.g., α-tocopherol and xanthophyll cycle antioxidants).…”
supporting
confidence: 65%
See 1 more Smart Citation
“…The O 3 HP site was created in 2009 in order to study the impact of climate change on a Q. pubescens forest. Using a rainfall exclusion device (an automated monitored roof deployed during chosen rain events) set up over part of the O 3 HP canopy, it was possible to reduce natural rain by 30 % and to extend the drought period in an attempt to mimic the current climatic model projections for 2100 (Giorgi and Lionello, 2008;IPCC, 2013;Polade et al, 2014). Two plots were considered in the site: a plot receiving natural precipitation where trees grew under natural drought (300 m 2 surface, used as control plot) and a second plot submitted to amplified drought (232 m 2 surface).…”
Section: Experimental Sitementioning
confidence: 99%
“…Likewise, the capacity of current L + T and T algorithms to predict emission shifts under different drought scenarios in the context of climate change needs to be addressed for isoprene and highly volatile compounds. This is of particular interest for the Mediterranean area where the most severe climatic scenario of the IPCC predicts an intensification of summer drought consisting of a rain reduction that could locally reach 30 %, an extension of the drought period as well as a temperature rise of 3.4 • C (Giorgi and Lionello, 2008;IPCC, 2013;Polade et al, 2014) for 2100.…”
mentioning
confidence: 99%